Jets from Young Stars II Clues from High Angular Resolution Observations - Bacciotti, Francesca; Whelan, Emma; Testi, Leonardo (Lecture Notes in Physics, 2008)
This volume contains the edited lecture notes of the Second JETSET School on Jets from Young Stars: Clues from High Angular Resolution Observations organised by the Marie Curie Research Training Network JETSET: Jet Simulations, Experiments and Theory. After the opening two chapters on jet emission, readers can learn the fundamental background of modern high-spatial-resolution techniques, and how such methods have impacted on our understanding of young stars. The lectures provide hands-on insight into Observing from space, e.g. from HST and in the future JWST, and from the ground with adaptive optics, The use of interferometers at millimetre and infrared wavelengths, Spectro-astrometry Image analysis and spectral diagnostic techniques High-Angular Resolution studies of the inner regions of circumstellar disks, which play a fundamental role in jet launching. The books' practical approach makes it an outstanding and extremely useful textbook for PhD students and young researchers in astronomy.